2012
DOI: 10.6064/2012/548150
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inflammatory Pathways in Cancer and Infectious Disease of the Cervix

Abstract: Cervical cancer is one of the leading gynaecological malignancies worldwide. It is an infectious disease of the cervix, associated with human papillomavirus infection (HPV), infection with bacterial agents such asChlamydia trachomatisandNeisseria gonorrhoeaas well as human immunodeficiency virus (HIV). Furthermore, it is an AIDS-defining disease with an accelerated mortality in HIV-infected women with cervical cancer. With the introduction of robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 80 publications
(101 reference statements)
0
24
0
2
Order By: Relevance
“…COX-2 is an enzyme with an imperative role in the metabolism of arachidonic acid, which leads to the production of prostaglandins, which in turn promote inflammation [32]. In fact, COX-2 is over-expressed in several malignancies, including cervical cancer [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 is an enzyme with an imperative role in the metabolism of arachidonic acid, which leads to the production of prostaglandins, which in turn promote inflammation [32]. In fact, COX-2 is over-expressed in several malignancies, including cervical cancer [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Of all HPV positive women, approximately 15% develop a persistent infection of the cervical epithelium [76]. Persistent HPV infections may slowly progress to cervical low-and highgrade squamous intraepithelial lesions (LSIL, HSIL) with the potential to develop to invasive squamous cell carcinoma (SCC) [77], Figure 5.…”
Section: Cervical Hpv Lesionsmentioning
confidence: 99%
“…Persistent HPV infections may slowly progress to cervical low-and highgrade squamous intraepithelial lesions (LSIL, HSIL) with the potential to develop to invasive squamous cell carcinoma (SCC) [77], Figure 5. Cofactors increasing the risk of progression are a compromised immune system and other co-infections such as HSV 2, Chlamydia trachomatis, Neisseria gonorrhoeae and BV [76,78,79]. Prolonged use of oral contraceptives (OC), high parity and smoking are other risk factors for persistent infection [80].…”
Section: Cervical Hpv Lesionsmentioning
confidence: 99%
“…It has been shown that persistent infection with high-risk HPVs leads to an increase in pro-inflammatory cytokines, including IL-6, TNF-α and MIP-1α [13]. In addition, high-risk HPV type 16 (HPV16) is able to increase the expression of cyclooxygenase-2 (COX-2), a key enzyme in the synthesis of prostaglandins, which are important mediators of inflammation [14,15]. Until now, only a single study has reported HPV DNA sequences in CSOM, whereby different HPV genotypes, including HPV16, HPV18 and HPV6, have been detected in 30.7% of CSOM [4].COMC is a form of expanding growth consisting of keratinizing squamous cell epithelium [16].…”
mentioning
confidence: 99%